A new type of integral bridge comprising geosynthetic-reinforced soil walls. Issue 4 (1st August 2009) - Soma, R.; Tatsuoka, F.; Tateyama, M.; Hirakawa, D.; Watanabe, K.; Aizawa, H.; Nojiri, M.; Nishikiori, H.
Abstract : ABSTRACT: Integral bridges, comprising a continuous bridge girder (i.e. deck) integrated to a pair of abutments without using hinged and movable shoes (i.e. bearings), have been constructed to alleviate several inherent drawbacks of conventional bridges. It is shown that this conventional type of integral bridge still has the following problems: (1) large residual settlements in the backfill, developing a bump immediately behind the abutments, and the development of high residual earth pressure on the back of the abutments by seasonal thermal expansion and contraction of the girder, as well as by traffic loads on the backfill; and (2) large detrimental deformation of the backfill by seismic loads. To alleviate these problems, it is proposed to reinforce the backfill with geosynthetic reinforcement that is firmly connected to the full-height rigid facings (i.e. abutments). A newly proposed integral bridge, called the GRS integral bridge, is constructed in stages: first, geosynthetic-reinforced backfill; second, pile foundations (if necessary); third, full-height rigid (FHR) facings (i.e. abutments); and finally a continuous girder integrated to the top of the two abutments, without using shoes. A series of static cyclic loading tests, laterally on the facing and vertically on the crest of the backfill, and shaking-table tests were performed on models of the conventional and new types of integral bridge, as well as two conventional bridge types comprising RC gravity-type abutments and geosynthetic-reinforced soil-retaining walls, both supporting a girder via shoes. The test results showed high static and dynamic performance of the GRS integral bridge, despite its simple structure and construction procedure, and therefore its low construction cost.